2005
DOI: 10.1111/j.1472-765x.2005.01692.x
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of keratin and collagen containing wastes by newly isolated thermoactinomycetes or by alkaline hydrolysis

Abstract: Aims: The aim of this study was to develop a method for microbial degradation of indigenous keratin wastes and to compare it with a method of alkaline hydrolysis. Methods and Results: Native sheep skin and wool were chosen as a model mixture of collagen and keratin wastes discarded by the leather and fur industries. Suitable conditions were found for hydrolysis of this mixture by four newly isolated thermoactinomycete strains. Another set of experiments was carried out using alkaline hydrolysis of keratin wast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(85 citation statements)
references
References 21 publications
0
74
1
Order By: Relevance
“…keratin) in an autoclave [29] or by microwaves [30]. In this study, this method has been applied to hydrolyze collagen and other organic compounds using an autoclave.…”
Section: Introductionmentioning
confidence: 99%
“…keratin) in an autoclave [29] or by microwaves [30]. In this study, this method has been applied to hydrolyze collagen and other organic compounds using an autoclave.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to their insoluble nature, feathers are resistant to degradation by common microbial proteases. Thus, the several million tons of feathers generated annually by the poultry industry leads to troublesome environmental pollution and wastage of protein-rich reserve (Onifade et al, 1998;Gousterova et al, 2005;Grazziotin et al, 2006). Keratinase enzymes have been found to be an effective feather degrading enzyme useful for degradation of feather, hair and chicken wastes.…”
Section: Discussionmentioning
confidence: 99%
“…The non-conventional sources like wastes from agriculture, poultry, meat and fish industry have been exploited to meet the demand of lowcost protein foods. Studies have shown that keratin hydrolysates may serve as good organic fertilizers (Gousterova et al 2005) and as amino acid supplements for health foods and pet foods (Gupta and Ramnani 2006). Two keratinases produced by B. licheniformis PWD-1, i.e.…”
Section: Proteases For Processing Of Keratin Wastesmentioning
confidence: 99%